2007
DOI: 10.1016/j.jcrs.2007.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative topical indomethacin to prevent pseudophakic cystoid macular edema

Abstract: Nonsteroidal antiinflammatory drugs decreased the incidence of CME, and their efficacy increased when begun preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 13 publications
0
54
0
3
Order By: Relevance
“…In a masked multicenter RCT, Wittpenn et al [23] showed that at week 4, clinical/OCT CME developed in five of 278 patients who received perioperative prednisolone, and in none of 268 who also received ketorolac (P ¼ 0.032). Yavas et al [24] in an unmasked RCT with 189 patients, reported angiographic PCME in 0% who received preoperative and postoperative topical indomethacin, 15% of those who received indomethacin only postoperatively, and 33% of controls (P < 0.001). Another unmasked RCT of 98 patients demonstrated that ketorolac prophylaxis resulted in lower total macular volume compared with controls at 1 month after surgery (P ¼ 0.009), with 46.1% (P ¼ 0.030) macular swelling reduction [25].…”
Section: Nsaidsmentioning
confidence: 99%
“…In a masked multicenter RCT, Wittpenn et al [23] showed that at week 4, clinical/OCT CME developed in five of 278 patients who received perioperative prednisolone, and in none of 268 who also received ketorolac (P ¼ 0.032). Yavas et al [24] in an unmasked RCT with 189 patients, reported angiographic PCME in 0% who received preoperative and postoperative topical indomethacin, 15% of those who received indomethacin only postoperatively, and 33% of controls (P < 0.001). Another unmasked RCT of 98 patients demonstrated that ketorolac prophylaxis resulted in lower total macular volume compared with controls at 1 month after surgery (P ¼ 0.009), with 46.1% (P ¼ 0.030) macular swelling reduction [25].…”
Section: Nsaidsmentioning
confidence: 99%
“…31 Pre-operative risk factors include diabetes, uveitis, previous retinal vein occlusion, epitretinal membrane, use of topical prostaglandin analogues and cystoid macular oedema following fellow eye surgery. 32 Studies have shown that use of peri-operative topical non-steroidal anti-inflammatory (NSAID) medication in addition to, or even instead of, routine topical steroid drops, can lower the incidence of pseudophakic angiographic cystoid macular oedema, 33,34 however their use is not routine in most departments and some express concern with using multiple drops and the risks of drop toxicity. Some ophthalmologists add topical NSAIDs post-operatively for patients deemed to be more at risk of macular oedema, such as those with diabetic retinopathy but no consensus exists in terms of their use.…”
Section: Cystoid Macular Oedemamentioning
confidence: 99%
“…In our study, all patients were treated according to a standardized protocol established at the Institute of Ophthalmology, Catholic University ''Sacro Cuore-Policlinico A. Gemelli,'' Rome. However, several therapeutic choices have been suggested for the management of PCME, 5,12,[30][31][32][33][34] and there is not yet a general consensus among different proposals for the prevention or treatment of PCME. Assessment of the efficacy of the used therapeutic protocol was beyond the scope of this study, which aimed at evaluating the clinical use of SD-OCT in PCME.…”
Section: Discussionmentioning
confidence: 99%